AKIBAT DEKADENSI MORAL TERHADAP DEGRADASI LINGKUNGAN MENURUT WAHBAH ZUHAILI DALAM TAFSIR AL-MUNIR, Q.S AR-RUM: 41 - M. Syukron Mahendra; Adnan Nugraha (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2025)
This article discusses the meaning of fasād (corruption or damage) in Q.S. ar-Rūm: 41, along with Wahbah az-Zuhaili’s interpretation in Tafsir al-Munīr regarding the relationship between moral decadence and environmental degradation. The verse indicates that the corruption occurring on land and at sea is a direct consequence of human actions, especially acts of immorality, injustice, and violations of moral values. Wahbah az-Zuhaili explains that fasād encompasses not only physical damage—such as drought, floods, and natural disasters—but also social decay resulting from human wrongdoing. This approach aligns with the Islamic environmental ethics perspective, which sees environmental destruction as stemming from humanity's failure to fulfill its role as stewards (khalīfah) of the earth. The article emphasizes the importance of integrating moral and spiritual dimensions in efforts to protect the environment, as well as the need for collective awareness to return to Islamic teachings that stress balance and responsibility toward nature. Thus, moral decadence significantly contributes to the ongoing ecological crisis, and its restoration requires ethical reform and a renewed commitment to divine values.